PENGARUH PRICE DISCOUNT DAN STORE ATMOSPHERE TERHADAP EMOTIONAL SHOPPING DAN IMPULSE BUYING (Survei pada Konsumen Hypermart Grand Mall di Surakarta) - Ria Apriliyani; Marjam Desma Rahadhini; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
Hypermart Grand Mall Surakarta is one of the retail stores in Surakarta. The purpose of this study is to analyze and explain the effect of price discount and store atmosphere on emotional shopping and impulse buying, the indirect effect of price discount on impulse buying through emotional shopping, and the indirect effect of store atmosphere on impulse buying through emotional shopping. This type of research is a survey method conducted at the Grand Mall Surakarta Hypermart. Data sources are primary and secondary data. The research population was all consumers who had made a purchase at the Hypermart Mall Grand Surakarta. The sampling technique uses non-probability techniques with a purposive sampling method of 110 respondents. The analysis technique uses the analysis of Structural Equation Modeling (SEM). Validity test uses confirmatory factor analysis (CFA) and reliability testing uses the cronbach's alpha value. The results show that price discount affects emotional shopping, store atmosphere influences emotional shopping, price discount effect on impulse buying, store atmosphere has an effect on impulse buying, emotional shopping has an impact on impulse buying, price discount indirect effect on impulse buying through emotional shopping, and store atmosphere indirect effect on impulse buying through emotional shopping.